New tree-ring evidence for the Late Glacial period from the northern pre-Alps in eastern Switzerland. (15th April 2018) - Reinig, Frederick; Nievergelt, Daniel; Esper, Jan; Friedrich, Michael; Helle, Gerhard; Hellmann, Lena; Kromer, Bernd; Morganti, Sandro; Pauly, Maren; Sookdeo, Adam; Tegel, Willy; Treydte, Kerstin; et al.
Abstract: The rate and magnitude of temperature variability at the transition from the Last Glacial Maximum into the early Holocene represents a natural analog to current and predicted climate change. A limited number of high-resolution proxy archives, however, challenges our understanding of environmental conditions during this period. Here, we present combined dendrochronological and radiocarbon evidence from 253 newly discovered subfossil pine stumps from Zurich, Switzerland. The individual trees reveal ages of 41–506 years and were growing between the Allerød and Preboreal (∼13′900–11′300 cal BP). Together with previously collected pines from this region, this world's best preserved Late Glacial forest substantially improves the earliest part of the absolutely dated European tree-ring width chronology between 11′300 and 11′900 cal BP. Radiocarbon measurements from 65 Zurich pines between ∼12′320 and 13′950 cal BP provide a perspective to prolong the continuous European tree-ring record by another ∼2000 years into the Late Glacial era. These data will also be relevant for pinpointing the Laacher See volcanic eruption (∼12′900 cal BP) and two major Alpine earthquakes (∼13′770 and ∼11′600 cal BP). In summary, this study emphasizes the importance of dating precision and multi-proxy comparison to disentangle environmental signals from methodological noise, particularly during periods of high climate variability but low data availability, such as the Younger Dryas cold spell (∼11′700 and 12′900 cal BP). Highlights: A total of 253 subfossil pine stumps were discovered in Zurich, CH. Trees were growing between the Allerød and Preboreal ∼13′900–11′300 cal BP. The Swiss Late Glacial pines improve the longest EU tree-ring chronology. Combined dendro and radiocarbon dating provides insight into the Younger Dryas.